Insights into the complexity of chiral recognition by a three-point model - Bao, Xiaoying; Snurr, Randall Q.; Broadbelt, Linda J. (Microporous and mesoporous materials, 2013)
[Display omitted] ► We use a three-point model to model chiral adsorption. ► The three-point model explains the difficulty in predicting chiral adsorption. ► Conditions leading to predictable enantioselectivity are proposed. The three-point model and molecular simulation are used to understand the enantioselective adsorption of a homologous series of chiral compounds on a common chiral selector that is incorporated on a solid surface. We demonstrate how the enantioselectivity of homologous chiral compounds may go down, go up, remain the same, or even reverse. Conditions that lead to consistent enantioselectivity for homologous chiral compounds are also proposed.